Goblet cells dictate viral tropism and pathogenesis in nasal and intestinal mucosae - Wenqian Wang; Wenwen Chao; Hui Zeng; Rongfeng Tang; Ruiling Liu; Chengcheng Wang; Xuan Wu; Jiaxin Qi; Yunlei Cao; Yuchen Li; Qian Yang (Proceedings of the National Academy of Sciences, 2025)
Host determinants are critical for shaping the outcomes of viral mucosal infections and developing effective antiviral strategies. However, the regulatory roles of “nonsusceptible” mucosal cells remain unclear. Here, we show that while swine influenza and porcine epidemic diarrhea (PEDV) viruses infect piglet nasal and intestinal epithelia, each virus establishes efficient infection only in its preferred mucosal niche. Goblet cell activity significantly influences mucosal infection outcomes; increased mucus secretion effectively blocks viral entry, while its reduction facilitates viral dissemination. Notably, PEDV activates acetylcholine-cholinergic receptor muscarinic 3 signaling in submucosal enteric neurons to induce goblet cell-associated antigen passages. This mechanism enables the translocation of intestinal bacteria to the lamina propria in early infection, even when the epithelial barrier remains intact, triggering inflammation and exacerbating mucosal damage. Our findings emphasize the crucial role of goblet cells in controlling viral tropism and their potential as targets for developing effective broad-spectrum antiviral approaches.